Jade Hydrothermal Field, Okinawa Trough: First Discovery Of Ag-And Au-Rich Massive Sulphides In An Intracontinental Backarc Basin - P. E. Halbach (International Marine Minerals Society, 1989)
On June 26, 1988, the Jade Hydrothermal Field was discovered in the Okinawa Trough by the German RV Sonne. This research cruise has taken place within the scope of a German-Japanese cooperative project. The Okinawa Trough, located between the Ryukyu Island Chain and the east coast of China, is an active backarc-basin formed by extension within the continental lithosphere. The Ryukyu arc consists of a nonvolcanic outer arc, forming the main island chain and representing compressive highs of the Asian continental margin, and an inner arc with present-day volcanism in its northern part (Sibuet et al. 1988). The valleys and ridges of the trough are cut across by transverse faults, giving rise to younger volcanic intrusions. The Jade Hydrothermal Field was detected in a caldera-like structure. It is. located at about 27°15,0'N and 127°04,5'E with a maxi- mum water depth of about 1650 m. Data of heat flow measurements show a high anomaly in the cauldron basin with values ranging from around 100 to 800 mw/m2 (Halbach et al. 1989). The hydrothermal vent area was discovered in the northern part of the inside northeast slope of the cauldron in a water depth between about 1300 and 1500 m. We identified different varieties of hydrothermal